Islands of Perspectival Thought: A Case Study - Daniel Morgan (Ergo, An Open Access Journal of Philosophy)
This paper has two aims. The first concerns the question of whether there is any essential involvement of perspectival thought in intentional agency. I defend the view that the answer is ‘no’ for one kind of perspectival thought, and ‘yes’ for a different kind. Agency does not depend on de se thought, but it does depend on de nunc thought. The second aim of the paper is to defend a claim about the significance of this de se–de nunc contrast as a case study. I argue that the contrast is best explained by a picture on which different kinds of perspectival thought are seen as islands. On this picture, an account of the conceptual role of one kind of perspectival thought won’t settle much about any other kind of perspectival thought. The picture is proposed as a replacement for the standard picture, on which perspectival thought is seen as a natural cognitive kind.